Left frontal white matter atrophy links to timing mechanisms relevant for apraxia of speech: Neuroimaging: Other neurodegenerative disorders. (7th December 2020) - Bruffaerts, Rose; Schaeverbeke, Jolien; Grube, Manon; Griffiths, Timothy; Sunaert, Stefan; Vandenberghe, Rik
Abstract: Background: In patients with apraxia of speech (AOS), we observed impaired perceptual timing abilities, which lead us to propose a shared mechanism of impaired timing processing underlying both impaired perceptual processing and motor speech output [1]. Given that white matter damage is often observed in AOS, we here investigate whether white matter changes are related to impaired perceptual timing as one possible mechanism underlying AOS. Method: A psychoacoustic and multimodal neuroimaging analysis was performed in 12 patients with the nonfluent variant (NFV) of Primary Progressive Aphasia (PPA) with AOS, 11 patients with the semantic variant and 24 controls. During the four perceptual timing tasks (r1‐r4, [1]), participants had to detect the longer gap in pairs of tones (r1) or in a sequence of tones (r2) or discriminate between rhythmic sequences with a strongly (r3) or weakly (r4) metrical beat. Speech rhythm was quantified in connected speech by means of the normalized pairwise variability index (PVI). Deformation‐based morphometry (DBM) and diffusion tensor imaging (DTI) were acquired on a 3T MRI and processed using CAT12 and MRTRIX3, respectively. We determined Fractional Anisotropy (FA) and Mean Diffusivity (MD) values for the left Aslant tract, which is typically damaged in NFV. Result: Seventy‐five percent of NFV patients displayed impaired perceptual timing, specifically when discriminating between rhythmic sequences (r3‐r4, transformed to z‐scores, Figure 1). Impaired perceptual timing correlated with abnormal vowel lengthening (correlation of r3 and PVI of strong‐weak words: r = 0.65, P = 0.029). Moreover, left frontal white matter volume loss adjacent to the supplementary motor area (SMA) correlated with impaired perceptual timing (r3) in NFV (Figure 2, cluster‐level FWE‐corr. P<.05). MD in the left Aslant tract also correlated with perceptual timing in NFV (correlation with r3: r = 0.82, P = 0.026). Conclusion: A shared white matter substrate adjacent to the SMA links impaired perceptual timing and motor speech impairment. Our data indicates that impaired timing may be one of the neurocomputational mechanisms underlying AOS. Moreover, regional variations in left frontal lobe atrophy explain part of phenotypical heterogeneity in NFV. Resource: (1) Grube, Bruffaerts, Schaeverbeke et al., Brain 2016.